2006
DOI: 10.1515/znb-2006-0909
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Sulfoxide Containing Platinum(II) and Palladium(II) Chelate Complexes of Glyoxylic and Pyruvic Acid Thiosemicarbazones. A New Class of Cytotoxic Metal Complexes

Abstract: The complex [Cu(en) 2 (H 2 O)](sy) 2 (en)(H 2 O) 2 has been synthesized and characterized by its electronic and vibrational spectra. The molecular structure of the complex has been determined by X-ray diffraction methods. The complex crystallizes in the orthorhombic space group Pnma with unit-cell parameters a = 10.7236 (5), b = 20.4660(10), c = 14.4523(11)Å and Z = 4. In the cation, the Cu(II) ion has a distorted square pyramidal coordination with two bidendate (en) ligands forming the basal plane and a H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 1 publication
2
18
0
Order By: Relevance
“…Finally, in the case of 1 this was confirmed by single crystal X-ray diffraction [1]. Nevertheless, after careful examination of a crystal specimen of 1, a very small number of plate-shaped crystals (1a) were noticed in the mass of block-shaped crystals reported previously [1], and they were studied by X-ray crystallography. The results of this study, which we report here, revealed that the crystal form 1a does not contain DMSO of solvation.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Finally, in the case of 1 this was confirmed by single crystal X-ray diffraction [1]. Nevertheless, after careful examination of a crystal specimen of 1, a very small number of plate-shaped crystals (1a) were noticed in the mass of block-shaped crystals reported previously [1], and they were studied by X-ray crystallography. The results of this study, which we report here, revealed that the crystal form 1a does not contain DMSO of solvation.…”
Section: Introductionsupporting
confidence: 52%
“…The synthesis of 1 and the preparation of a crystalline sample for X-ray diffraction have been described in detail previously [1]. A plate-shaped crystal of 1a for the present study was selected from the same crystalline sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The coordination mode of the complexes in solution was determined by using the 1 H NMR spectra and the assignments of resonances were based on literature data [40,9] and are in good agreement with proposed structure. The numbering of protons used for 1 H NMR is shown in Scheme 2.…”
Section: Nmr Spectramentioning
confidence: 56%